THE IMPACT OF POWDERS AND OIL ADDITIVES OF CINNAMON AND CLOVE IN QUAILS DIET AS ANTISTRESSOR AND ANTIOXIDANT DURING HOT MONTHS - & Wasman, Mustafa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The present investigation was carried out to compare the impact of cinnamon and clove powders and their oil additives as anti-stressors on quails under heat stress which is one of the riskiest environmental conditions that influence poultry all over the world in general and Iraq in particular. For this purpose, 420 quails (5 weeks old) were chosen and randomly grouped into seven treatments with different treatments (T0: control (standard diet), T1: 2 g clove powder/kg diet, T2: 1 ml clove oil/kg diet, T3: 2 g cinnamon powder, T4: 1 ml cinnamon oil/kg diet, T5: 1 g clove powder+1 g cinnamon powder/kg diet, T6: 0.5 ml clove oil+0.5 ml cinnamon oil/kg diet) added to standard diet. The quails were fed with these diets for 17 weeks. The results indicated that adding clove, cinnamon, and their oils to quail diet under heat stress led to significantly (p